(untitled) (Research, Society and Development, 2020)
Passiflora foetida, a species of wild passion fruit, has been investigated due to its pharmaceutical potential and its agronomic characteristic of resistance to Fusarium spp., enabling its use as a rootstock for passion fruit species susceptible to premature death. Thus, in order to perform the propagation of this species, micropropagation is one of the most used forms, being necessary the use of accessions of a matrix plant to, by organogenesis, generate new seedlings with the same genotype. Thus, the aim of the present study was to establish a protocol for the in vitro propagation of P. foetida, inducing the buds of this plant, by organogenesis, testing two concentrations of mineral salts from MS medium, without addition of phytohormones. For in vitro establishment, apical and lateral buds obtained from plants of P. foetida, grown in a greenhouse, were used. The experiments were carried out in a completely randomized design. Sixty days after inoculation of explants, the following criteria were evaluated: number of buds, length of sprouting, number of leaves, coloration score, developmental score and root number. To guarantee the accuracy of the results, statistical techniques were applied to data analysis and optimization of results. The development of plants by organogenesis showed statistically similar values ​​in both concentrations, concluding that the MS medium with half concentrations of nutrients was considered the most viable for the in vitro establishment of this species.